Synthesis, Characterization and Antibacterial studies of Co(II), Ni(II) and Cu(II) Schiff Base complexes derived from Ethyl-methyl Ketone - Mishra, A.P.; Khare, Mahima (Asian Journal of Chemistry, 2010)
Complexes of Co(II), Ni(II) and Cu(lI) with Schiff base formedby condensation of 2-aminophenol and ethyl-methyl ketone havebeen synthesized and their physico-chemical properties have beeninvestigated by microanalytical, UV-Vis, IR spectral, conductance,TGA and magnetic measurements. The ligand field parameters ofthe complexes have also been calculated. The antibacterial activitieshave been tested. The complexes are of general formulae[MLCI2(H2O2].2H2O and [ML(H2O2].CI2·2H2O.